2016
DOI: 10.1002/dev.21493
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deprivation alters expression of neural maturation gene tbr1 in the amygdala paralaminar nucleus in infant female macaques

Abstract: Early parental loss is associated with social-emotional dysregulation and amygdala physiologic changes. Previously, we examined whole amygdala gene expression in infant monkeys exposed to early maternal deprivation. Here, we focus on an amygdala region with immature neurons at birth: the paralaminar nucleus (PL). We hypothesized that 1) the normal infant PL is enriched in a subset of neural maturation (NM) genes compared to a nearby amygdala subregion; and 2) maternal deprivation would downregulate expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 87 publications
(139 reference statements)
1
49
0
Order By: Relevance
“…It is plausible that differences in the environment shape social processing demands (Lambert et al, ; Lederbogen et al, ; Urakawa et al, ) and may have affected the trajectory of amygdala growth. This hypothesis is supported by a body of literature describing the impact of maternal deprivation on amygdala development and connectivity in human and nonhuman primates (de Campo et al, ; Gee et al, ; Olsavsky et al, ; Sabatini et al, ).…”
Section: Discussionmentioning
confidence: 74%
“…It is plausible that differences in the environment shape social processing demands (Lambert et al, ; Lederbogen et al, ; Urakawa et al, ) and may have affected the trajectory of amygdala growth. This hypothesis is supported by a body of literature describing the impact of maternal deprivation on amygdala development and connectivity in human and nonhuman primates (de Campo et al, ; Gee et al, ; Olsavsky et al, ; Sabatini et al, ).…”
Section: Discussionmentioning
confidence: 74%
“…The cellular architecture and the maturation of PL neurons could therefore be influenced by life experiences during these ages. A recent study found that in the macaque, early life maternal separation leads to lower levels of TBR1 gene expression in the PL later in life 35 . Which cells are affected in the PL and whether this is merely a correlation, or reflects lower amounts of activity in the PL or lower levels of cell maturation remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lesion studies of the macaque neonatal and adult uncal hippocampus have found fewer immature neurons and more mature neurons in the PL, implying a role for the hippocampal afferents on the maturation of these cells 34 . Early life stress also leads to lower levels of the excitatory neuron transcription factor T-box, brain 1 (TBR1) in the non-human primate PL 35 . A better understanding of the types of neurons in the PL, their relationship to adult neural stem cells, and their developmental dynamics is required to understand the implications of changes in neuropsychiatric disorders 10 and the relationship of the amygdala–hippocampal network to mood 27 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the exposure to stress in the postnatal period can trigger numerous effects on neuroplasticity, cognitive function, and behavior in adulthood [44], since the postnatal period is critical for the central nervous system development [4]. In this sense, strategies that seek to minimize and/or reverse cognitive damages related to this type of stress are important.…”
Section: Discussionmentioning
confidence: 99%
“…The early life stress causes neuroendocrine changes associated with social and emotional behavior alterations [2] that may persist throughout life [3]. In humans, especially from the prenatal period until the early years of postnatal life, the brain undergoes a rapid development [4] and is highly sensitive to the influence of positive and negative external experiences [5].…”
Section: Introductionmentioning
confidence: 99%